La quête d’autonomie résidentielle des femmes inuites du Nunavik : une perspective relationnelle - Hervé, Caroline; Laneuville, Pascale (Recherches amérindiennes au Québec, 2024)
This article explores the quest for residential autonomy for Inuit women of Nunavik through a relational perspective. Based on testimonies of women on the housing shortage, it shows the links between overcrowded houses and family violence. It pinpoints the limits of the social housing program in situations where women try to escape from unhealthy relationships. Far from reflecting a desire for emancipation and breaking off, this quest for autonomy should be rather understood as an attempt to obtain a safe environment for them and their family and the attempt to rebuild new healthy relationships. The interest in developing such a relational perspective on the housing issue invites us to understand how contemporary social housing programs provide, following Ingold’s distinction, buildings rather than dwellings.